Blended Learning as a Developmental Model Strategy of Teaching and Learning in Islamic Universities in Indonesia - Khairul Saleh; Ity Rukiyah; Muhammad Arbain (Dinamika Ilmu, 2021)
Blended learning is a demanding topic nowadays where its existence is possibly enhance lecturers’ competencies as well as giving students new experiences from the combination of different platforms of learning i.e. face to face interaction and online class. Since blended learning seems to be relevant topic at the present time, therefore the aim of the study is to explore the implementation of blended learning in Islamic universities in six different cities in Indonesia. Direct observation was conducted in order to map the strategy used by each Islamic university in implementing blended learning method. Other than that, Focus Group Discussion was also held to all Islamic universities in order to dig deeper regarding the policy from the management of the study program of Pendidikan Agama Islam (PAI) as well as confirming to what researchers found on the direct observation to the lecturers related to blended learning employment. Additionally, to support the result, semi-structured interview was conducted to representative of students from each Islamic university in order to highlight their perspectives in the realization of blended learning. As a result, the researchers found that the proportion of having between offline and online learning methods are varied, whether 70:30, 60:40, or 50:50. Additionally, there is no slight difference in terms of conducted activities during the offline session, whereas the use of online platforms with varied e-learning media are found very interestingly. Lastly, interview conducted to PAI students indicate positive attitude towards the implementation of blended learning where it is obviously provide future insight for further researchers. The novelty and pedagogical implications are also highlited in this article.